Antioxidant, Antimicrobial, Cytotoxicity and HPLC Studies of Sophora mollis - Iram1, Humera; Rasool1, Nasir; Riaz1, Muhammad; Zubair1, Muhammad; Rashid2, Umer; Hussain Bukhari1, Iftikhar; Bakhsh Tareen3, Rasool; Saiful Islam4, Md. (Asian Journal of Chemistry, 2013)
The present study was undertaken to evaluate the antioxidant activities of plant extract/fractions. Total phenolic contents value ranged from 5.69 to 39.36 for stem and 5.50 to 118.8 GAE (mg/100 g) for leaves while total flavonoid contents value ranged from 6.81-261.00 for stem and 26.16-91.04 CE (mg/100 g) for leaves of S. mollis. The highest total phenolic contents value was showed by ethyl acetate fraction (118.80 mg/100 g) of leaves and ethyl acetate fraction (261.00 mg/100 g) of stem showed highest total flavonoid contents value. The lowest IC50 value was exhibited by ethyl acetate fraction (17.77 μg/mL) of leaves. The maximum % inhibition of peroxidation in linoleic acid system was observed in ethyl acetate fraction (91.54 %) of leaves. The methanolic extract and its different fractions were explored to antimicrobial activity by using disc diffusion method. The maximum antibacterial activity was shown by n-butanolic fraction against Bacillus cereus. From the present investigation, the haemolytic effect of plant was found to be in the range of 1.40 to 14.31 % for stem extract/fractions from 2.34 to 16.56 % for leaves extract/fractions of S. mollis. From HPLC analysis of some extract and fractions of plant different phenolic constituents were identified. From this research work it is concluded that this plant could be used as natural antioxidant and antimicrobial agents and medicinally very important.